Sic Utere Tuo Ut Alienum Non Laedas: State Responsibility and Environmental Obligations in the Context of Climate Change - Atika Sari, Diah Apriani; Triatmodjo, Marsudi; Purwanto, Harry (Yustisia, 2025)
The principle of Sic utere tuo ut alienum non laedas requires the state to avoid environmental damage and to prevent harmful activity on its territory. UNFCCC laws restrict states from emitting excessive greenhouse gases. Avoiding environmental damage is crucial to protecting against losses and mitigating global warming in the context of climate change. This study aimed to examine of the interplay between the principle of Sic utere tuo ut alienum non laedas, the duty to refrain from environmental degradation, and the responsibility of tackling climate change. The results show that the state caused increasing sea levels, melting glaciers and polar ice, and unpredictable hydrological cycles due to enormous greenhouse gas emissions.  Climate change was less important than the sovereign right to develop and explore natural resources.  International legislative tools like the Climate Change Convention slowed climate change. International law requires environmental protection under sic utere tuo ut alienum non-laedas. Climate change conventions did not accept this principle. In Anglo-Saxon law, sic utere tuo ut alienum non laedas—the principle of no harm—required state accountability for international law infractions and restitution.  The state was held accountable under international law for excessive greenhouse emissions under strict liability.